Ironia w socjolekcie uczniowskim - Bortliczek, Małgorzata (Stylistyka, 2021)
Article appeals to lexical and idiomatic material outstanding pupil’s dialect among other types of slang in Polish language. Analyse of selected components of structural and semantic neologisms register, lead to conclusions relating mechanisms of creation derivatives (of extending of lexical supply) in youth jargon. In structural word-formation exist system and out of system formants added to characterised by emotionally of formative bases. Semantic derivation leans on associations releasing schema SOMEBODY / SOMETHING SMALL / SMALLER (LESS) VALUES. In effect, collection of structural and semantic neologisms is dominated by words and idioms ironically (often vulgarly) characterised. Using of metaphors, appealing e.g. to military, prison, eschatological association and stereotypes, simplifying estimation of people and facts, helps to bringing to light by jargon users ironical relation to realities. Pupils’ environment creates specific community of fun, founding ironical treatment of people, facts or events, because of some reason in relation to introducing SMALL/SMALLER (LESS) VALUE.